PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XII IPA SMAN 16 PADANG - Rahmi, Irvani; Rahmi, Rahmi; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTThis research based on the phenomenon of student study and comprehen math concept. Their understanding was still low. It made them unactive. This research wants to describe student grade XII for science departement in their learning activity. It also wants to know wheter their understanding of math concept using active learning strategies type quiz team with handout is better than conventional learning. This was an experimental research, it used random research design toward the subject. The instrument used in this research is the observation form and test for students understanding of math concepts. The results of research shows that the positive activity of students in learning mathematics using active learning strategies type quiz team and handouts has increased, while the negative activity has decreased in every meeting. Hypothesis test results obtained P-value = 0.006 was smaller than Î± = 0.05, indicating that the hypothesis was accepted. So, it was concluded that the students understanding of math concepts by applying active learning strategies type quiz team with handouts better than students understanding of the math concepts with conventional learning. Â